Biofilm Formation Capacity of Bacterial Isolates from Kitchen Sponges - Amadi-Ikpa, C.N.; Okwelle, A.A. (International Journal of Advanced Technology and Social Sciences, 2023)
This study was aimed at determining biofilm forming bacteria isolates in kitchen sponges of some homes. The investigation involved collection of kitchen sponges from homes before and after the sponges have been used, and thereafter standard microbiological procedure was adopted. Analysis employed   the spread plate count and the streak plate techniques. Counts of the bacterial isolates after a 24 hours incubation at 35 degrees centigrade were observed on freshly prepared nutrient agar, Salmonella/Shigella agar, Mannitol salt agar and MacConkey agar media that have been plated with the sample. Also isolates recovered were identified and streaked on Congo red media. Results obtained showed heavy colony counts on nutrient agar plates, Salmonella/Shigella agar plates, Manitol salt agar plates with counts above 103CFU/g. Biochemical identification of the isolates recovered four (4) bacteria species out of a total of 19 isolates from the study namely ; Staphylococcus aureus, Proteus spp., Shigella spp. and Salmonella spp. Proteus spp. were observed with heavy biofilm formation while Shigella spp. was least, Staphylococcus aureus also expressed biofilm property. Result thus indicated that sponge contact on dishes possess some risk to dish users, due to persistence of biofilm expressed by bacteria isolates even after sponge disinfection with Sodium Hypochlorite. This further suggests that kitchen sponges may play a critical role in the health of household occupants and therefore be discarded after every use